ETHNOMEDICIAL STUDY OF TRADITIONAL INDONESIAN MEDICINAL PLANT - Wiwit Zuriati Uno; Aditya Kuengo; Alvionita B. Anwar; Faizha Putri Delia (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
The title of study is Ethnomedicial Study Of Traditional Indonesian Medicinal Plant. This study aimed to review the ethnomedicinal use of moringa leaves (Moringa oleifera Lam.) among Indonesian communities and to analyze its relevance to scientific evidence related to phytochemical composition, pharmacological activities, and safety aspects. The research employed a literature review method with a descriptive-analytical approach by examining scientific articles, ethnomedicinal books, and research reports obtained from Google Scholar, PubMed, and ScienceDirect databases. The results indicate that moringa leaves are traditionally used to maintain health, enhance immune function, promote lactation, reduce inflammation, and assist in blood glucose management. Scientific findings support these traditional uses through the identification of bioactive compounds and relevant pharmacological activities, while also indicating that moringa leaves are generally safe when consumed at traditional doses. This study highlights the importance of ethnomedicine as a scientific foundation for the rational development of evidence-based traditional medicine.